Analysis of Potential Hazards in the Mining Area of PT Cakrawala Prima Manunggal Using the Hira Method - Muhammad Rafi Kaldi; Rodiyah Nursani; Suhardiman Gumanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Mining activities involve various potential hazards that may cause occupational accidents, requiring systematic efforts to identify, assess, and control workplace risks. This study aims to identify potential hazards, analyze risk levels, and formulate risk control recommendations in the mining production area of PT Cakrawala Prima Manunggal. The study employed the Hazard Identification and Risk Assessment (HIRA) method through field observations, interviews, documentation, and literature review. Hazard identification was conducted across six operational areas, namely the workshop, parking area, front loading, main road hauling, disposal dumping, and stock ROM. Risk assessment was performed by evaluating likelihood and severity using the AS/NZS 4360 risk matrix. The results identified 17 potential hazards, consisting of 10 high-risk hazards (59%), 6 medium-risk hazards (35%), and 1 low-risk hazard (6%). High-risk hazards were primarily associated with road conditions, equipment maneuvering areas, safety berms, dust exposure, inadequate illumination, and disposal-area conditions. Recommended controls include the proper use of personal protective equipment, installation of safety signs and barriers, improvement of road and workplace conditions, dust suppression through water spraying, workplace organization, strengthened supervision, and continuous safety education and implementation of occupational safety and health procedures. These findings provide a systematic basis for prioritizing preventive interventions and strengthening occupational risk management in mining operations.